Multi-Actor Governance of Waste-to-Energy: A Case Study of the Putri Cempo Waste-to-Energy Power Plant in Surakarta City - Rosi, Syavina Damar; Sandria, Andriko (Tecno Scientifica Publishing, 2025)
This research examined the dynamics of governance in waste management through a case study of the Putri Cempo waste-to-energy (WTE) power plant. The growing volume of global waste has driven the need for multi-level governance to advance WTE technology. The application of WTE technology became part of the national commitment to climate change mitigation outlined in the Nationally Determined Contribution (NDC) framework. The development of WTE also contributed to the attainment of several Sustainable Development Goals (SDGs), notably SDG 7 (Affordable and Clean Energy) and SDG 13 (Climate Action), by providing renewable energy and reducing greenhouse gas emissions. The main focus was to analyse how multi-actor governance was implemented in WTE management practices at the local level, as well as the challenges that arose in ensuring operational sustainability. Employing a descriptive qualitative approach, this study adopted a multi-actor and institutional governance perspective and applied Biermann’s Five A’s concept, architecture, agency, adaptiveness, accountability, and allocation, as the analytical framework for mapping the governance situation of the Putri Cempo WTE facility. The findings indicated that despite regulatory support, including Presidential Regulation No. 35 of 2018 and Indonesia’s enhanced NDC targets, the implementation of the Putri Cempo WTE still faced technical challenges, particularly high moisture content specifications and inadequate waste sorting, which disrupted the gasification process. In addition, the surrounding community reported environmental problems. Increasing technical capacity, developing an effective waste-sorting system, and ensuring more transparent environmental monitoring by managers and supervisors were needed to support the long-term sustainability of waste-to-energy power plant operations.